Lithium ion battery performance enhancer as well as preparation method and application thereof

By using biomass carbon fiber as performance enhancer in lithium-ion batteries, a three-dimensional topological frame conductive network structure is formed, and the mechanical stress problem caused by changes in the anode material volume is solved, which significantly improves the cycle life and capacity of the battery and reduces safety risks.

CN119812328APending Publication Date: 2025-04-11HANGZHOU TIANYICHENG CHEM EQUIP +1
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411868661.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-18
Publication Date
2025-04-11

AI Technical Summary

Technical Problem

Mechanical stress problems caused by changes in the volume of the anode material during long-term circulation of lithium-ion batteries may cause safety risks, such as the battery bulging or rupture, which in turn triggers combustion and explosion.

Method used

Biomass carbon fiber is used as the performance enhancer of lithium-ion batteries, and a three-dimensional topological frame conductive network structure is formed by mixing it with active substances, dispersing the volume change stress during the electrode deintercalation process, enhancing the electrode mechanical properties and the electronic conductivity of the active substances.

Benefits of technology

Effectively disperse the internal stress of the electrode, suppress material expansion, improve electron conduction rate, extend the cycle life of the battery, improve the first circle of the battery, reduce the contact resistance of the electrode, and promote the infiltration of the electrolyte against the electrode sheet.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119812328A_ABST
    Figure CN119812328A_ABST
Patent Text Reader

Abstract

The invention provides a lithium ion battery performance enhancer as well as a preparation method and application thereof, and relates to the field of battery negative electrode materials. The reinforcing agent is made of biomass carbon fiber, the biomass carbon fiber is of a hollow structure, and micropores are formed in the surface of the biomass carbon fiber. The lithium ion battery performance enhancer can effectively disperse internal stress of an electrode and inhibit material expansion; the composite material can effectively improve the electronic conductivity of the material, and plays a role in collecting micro-current between active substance particles and between the active substance particles and a current collector, so that the contact resistance of an electrode is reduced, the polarization of the battery is reduced, and the infiltration of an electrolyte on a pole piece is promoted.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of battery materials, and in particular to a lithium ion battery performance enhancer and a preparation method and application thereof. Background Art

[0002] Lithium-ion batteries (LIBs) have revolutionized the energy storage landscape due to their high energy density and long cycle life. However, the volume change of both graphite (about 15%) and silicon (about 300%) anodes poses a safety risk to batteries during long-term cycling. Emerging silicon-based anode materials face even greater problems, withstanding pressures up to 0.2 GPa. Excessive mechanical stress may cause the electrode to deform or expand, raising safety issues. Worse still, this may cause the battery to bulge or rupture, exposing the reactive electrode and flammable carbonate electrolyte to air, which may trigger combustion and explosion. Solving the volume expansion problem of anode materials is an application in recent years to cope with the huge volume change of silicon-based materials. In recent years, in order to cope with the huge volume change of silicon-based materials, nanoscale engineering design has been used to shrink bulk silicon to a critical size of less than 150 nanometers. However, the low compaction density, high cost and low yield synthesis of nanosized materials have limited the expansion of commercial scale. Based on the theory of fiber-reinforced materials, combining fiber fillers with matrix can achieve the best balance of mechanical strength and functionality. When subjected to external forces, the fibers directly bear the stress and transfer it to other fibers through interfacial interactions (e.g., mechanical interlocking, chemical bonding), thereby reducing the stress burden on the matrix. The multi-directional fiber configuration enables the fibers to not only bear tensile loads in their own direction, but also share part of the stress in other directions, thereby promoting a uniform distribution of stress. Fibers can also inhibit crack propagation through a "bridging" effect. When cracks propagate in the matrix, the fibers are able to locally reinforce the crack area and limit the propagation of the crack by interacting with the crack. Introducing fibers into negative electrode materials is expected to enable the electrode to accommodate huge volume changes.

[0003] In recent years, with the growing demand for environmentally friendly lithium-ion battery materials, biomass carbon materials have attracted widespread attention due to their sustainability and low carbon footprint. A variety of biomass resources, such as cotton fiber, bamboo fiber and wood fiber, can be prepared into carbon fibers through a specific preparation process. Studies have shown that these biomass carbon fibers have good mechanical strength and conductivity and have good application prospects in lithium-ion batteries. Therefore, it is of great significance to study the application of biomass carbon fibers in lithium-ion battery performance enhancers. Summary of the invention

[0004] To solve the above problems, the present invention provides a lithium ion battery performance enhancer and its preparation method and application. The lithium ion battery performance enhancer has the function of dispersing the volume change stress during the process of electrode lithium ion insertion and extraction, and enhancing the mechanical properties of the electrode and the electronic conductivity of the active material.

[0005] The technical solution adopted by the present invention is as follows:

[0006] A lithium-ion battery performance enhancer, the lithium-ion battery performance enhancer is a biomass carbon fiber, the biomass carbon fiber is a hollow structure, and has micropores on the surface. The lithium-ion battery performance enhancer can be mixed with an active substance to form a three-dimensional topological framework conductive network structure. The material has a large specific surface area, abundant active sites, uniform tube diameter distribution, and excellent conductivity. The addition of hollow tubular biomass carbon fibers can not only improve the first-cycle coulomb efficiency and capacity of the battery, but also disperse the expansion stress and increase the electron conduction rate, thereby effectively solving the problems of low capacity, short cycle life, and poor cycle stability of lithium-ion batteries in the prior art.

[0007] Furthermore, the micropores are obtained by high-temperature carbonization.

[0008] Further, the wall thickness of the biomass carbon fiber is 0.0001 μm to 20 μm, the diameter is 0.01 μm to 50 μm, the length is 5 μm to 100 mm, and the aspect ratio is not less than 2. Preferably, the diameter of the biomass carbon fiber is 10 μm to 30 μm, and the length is 10 μm to 500 μm. The biomass carbon fibers have similar diameters, have stable chemical bonds, and are conducive to uniform dispersion.

[0009] Furthermore, the active material is one or more of graphite negative electrode materials or silicon-based negative electrode materials (silicon materials, silicon-oxygen materials, silicon-carbon materials, etc.).

[0010] A method for preparing the above-mentioned lithium ion battery performance enhancer, the preparation steps are as follows:

[0011] (1) mixing an oxidant and an oxidizing aid evenly, adding biomass fibers, stirring at a certain temperature, washing with alcohol, and drying to obtain a precursor;

[0012] (2) calcining the precursor under an inert atmosphere to obtain biomass carbon fiber, i.e., the lithium ion battery performance enhancer.

[0013] Furthermore, the oxidant is one or more of sodium hydroxide, potassium hydroxide, sodium chlorite, sodium hypochlorite, and hydrogen peroxide; the oxidant is one or more of acetic acid, citric acid, and phosphate buffer. The oxidant and oxidant can remove impurities on the surface of biomass carbon fiber and ensure that the original morphology of the fiber remains unchanged during the treatment process.

[0014] Furthermore, the biomass fiber is one or more of the biomass native fiber of Malvaceae, Bombacaceae, Urticaceae, Palmaceae, Gramineae, biomass regenerated fiber and biomass synthetic fiber, preferably the biomass native fiber of Malvaceae.

[0015] Furthermore, the alcohols include, but are not limited to, one or more of methanol, ethanol, propylene glycol, butylene glycol, pentanediol, and hexanediol.

[0016] Furthermore, the mass ratio of the biomass fiber to the oxidant is 1:2 to 1:100; the mass ratio of the oxidant to the oxidizing aid is 1:1 to 1:50.

[0017] Furthermore, the drying temperature is 5°C to 120°C, and the drying time is 0.01h to 120h; the calcination temperature is 100°C to 1200°C, and the calcination time is 0.01h to 120h.

[0018] A negative electrode slurry for lithium ion batteries, wherein the negative electrode includes but is not limited to a graphite negative electrode, a silicon oxygen negative electrode, a silicon carbon negative electrode, etc. The above-mentioned lithium ion battery enhancer is added to the negative electrode slurry, and the lithium ion battery performance enhancer accounts for 0.0001-10% of the total mass of the negative electrode slurry.

[0019] A lithium ion battery comprises the above-mentioned negative electrode slurry and an electrode material, a battery or an electrochemical device prepared by the preparation method.

[0020] Compared with the prior art, the present invention has the following beneficial effects:

[0021] (1) The lithium-ion battery performance enhancer of the present invention is a biomass carbon fiber with a diameter of 0.01 μm to 50 μm and micropores on the surface with a diameter of less than 2 nm. The biomass carbon fiber can be mixed with active substances to form a three-dimensional topological framework network structure. When subjected to external force, the fiber directly bears the stress and transfers it to other fibers through interface interactions (e.g., mechanical interlocking, chemical bonding), thereby reducing the stress burden on the matrix.

[0022] (2) The lithium-ion battery performance enhancer of the present invention can not only improve the first-cycle coulomb efficiency and capacity of the battery, but also effectively disperse the internal stress of the electrode, inhibit material expansion, and effectively improve the electronic conductivity of the material.

[0023] (3) The lithium-ion battery performance enhancer of the present invention can collect microcurrents between active material particles and between active material particles and current collectors, thereby reducing the contact resistance of the electrodes, lowering battery polarization, and promoting the infiltration of the electrolyte into the electrode sheets, thereby effectively solving the problems of low capacity, short cycle life, and poor cycle stability of lithium-ion batteries in the prior art.

[0024] (4) The raw materials of the present invention are green and environmentally friendly, the preparation process is simple, the operation is convenient, and it is easy to realize large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 The figure is a flow chart of the preparation of the lithium-ion battery performance enhancer in an embodiment of the present invention.

[0026] Figure 2 The three-dimensional topological framework network structure cross-sectional morphology scanning electron microscope image (SEM) (a) and surface morphology scanning electron microscope image (SEM) (b) of the electrode in Example 4 of the present invention are shown.

[0027] Figure 3 SEM images of the biomass carbon fibers prepared in Example 1 of the present invention and the carbon fibers prepared in Comparative Example 1.

[0028] Figure 4 These are SEM images of the precursors prepared in Example 1 of the present invention and Comparative Examples 2-3.

[0029] Figure 5 This is the SEM image of the biomass carbon fiber prepared in Examples 1-3 of the present invention.

[0030] Figure 6 This is a pore size distribution diagram of the biomass carbon fibers prepared in Examples 1-3 of the present invention.

[0031] Figure 7 These are cross-sectional SEM images of different silicon-oxygen electrodes of Example 4 and Comparative Example 5 of the present invention before cycling, after cycling for 10 cycles at 0.5C, and after Li+ embedding for 50 cycles.

[0032] Figure 8 The SEM images of the electrode surfaces of Example 4 and Comparative Example 5 of the present invention after 50 cycles at 0.5C are shown.

[0033] Fig. 9 It is a comparison diagram of the four-point probe conductivity of the negative electrode sheets of Example 4 of the present invention and Comparative Example 5 under different pressures.

[0034] Fig.10 This is a battery cycle performance diagram of Example 4 of the present invention and Comparative Example 5.

[0035] Fig.11 This is a battery rate performance diagram of Example 4 of the present invention and Comparative Example 5. DETAILED DESCRIPTION

[0036] In order to facilitate the understanding of the lithium ion battery performance enhancer of the present invention, the lithium ion battery performance enhancer of the present invention will be described in more detail below. Examples of the present invention are given, but the scope of the present invention is not limited thereby. The present invention will be further described below in conjunction with the examples.

[0037] Example 1

[0038] like Figure 1 As shown, a lithium-ion battery performance enhancer, the preparation steps are as follows:

[0039] (1) Weigh 100 g of 1% sodium chlorite solution, add 1 mL of acetic acid, mix well, add 1 g of bamboo fiber, stir at 80° C. for 2 h, wash with ethanol and dry to obtain a precursor;

[0040] (2) The precursor was heated to 150°C at a heating rate of 2°C / min under an argon atmosphere and calcined for 2 h, and then heated to 800°C at a heating rate of 5°C / min and calcined for 2 h to obtain biomass carbon fiber, i.e., a lithium ion battery performance enhancer (its SEM image is shown in FIG. Figure 5 (as shown in (a)).

[0041] Example 2

[0042] The difference from Example 1 is that in step (2), the heating rate of 5°C / min to 800°C is changed to the heating rate of 5°C / min to 600°C. The SEM image of the biomass carbon fiber prepared in Example 2 is as follows: Figure 5 (b) as shown.

[0043] Example 3

[0044] The difference from Example 1 is that in step (2), the heating rate of 5°C / min to 800°C is changed to the heating rate of 5°C / min to 1000°C. The SEM image of the biomass carbon fiber prepared in Example 3 is as follows: Figure 5 (c) as shown.

[0045] from Figure 5 It can be seen from the figure that the carbonized fiber is in the shape of a flat tube. As the temperature increases from 600℃ to 1000℃, the fiber wrinkles increase and the tube diameter becomes ~10μm.

[0046] The lithium ion battery performance enhancer prepared by the present invention has micropores on its surface, with a pore size of less than 2nm. Figure 6 This is the pore size distribution diagram of the biomass carbon fiber prepared in Examples 1-3, where the peak intensity represents the number of pores. It can be seen from the figure that the peak intensity is the largest near 1.5 nm, indicating that the micropore distribution of the biomass carbon fiber is mainly concentrated at 1.5 nm.

[0047] Embodiment 4-6

[0048] The lithium ion battery performance enhancer obtained in Example 1-3 was mixed in water in a mass ratio of silicon oxygen active material: lithium ion battery performance enhancer: carbon black (SP): PAA (polyacrylic acid) = 80%: 3%: 7%: 10% to form a uniform negative electrode slurry, and then coated on copper foil and dried to form a negative electrode sheet.

[0049] Assembled battery: The CR2025 button cell was assembled in a glove box with an argon atmosphere. For the button half-cell, pure metal lithium sheet was used as the electrode, Celgard 2325 type was used as the diaphragm, and the electrolyte was a mixed solution containing 1.2M lithium hexafluorophosphate (LiPF6), ethylene carbonate (EC), diethyl carbonate (DEC) (where EC / DEC = 1 / 1, v / v) and 25vol% fluoroethylene carbonate (FEC). The charge and discharge tests were carried out on the LAND electrochemical test system in Wuhan, China. For the half-cell, the charge and discharge voltage window was 0.005-1.5V.

[0050] Figure 2 The three-dimensional topological framework network structure cross-sectional morphology and surface morphology scanning electron microscope (SEM) of the electrode in Example 4, it can be seen from the figure that the biomass carbon fiber is used as the skeleton structure of the electrode inside the electrode structure. When subjected to external force, the fiber directly bears stress and transmits it to other fibers through interface interaction (e.g., mechanical interlocking, chemical bonding), thereby reducing the stress burden on the matrix. The multi-directional fiber configuration enables the fiber to not only bear tensile loads in its own direction, but also share part of the stress in other directions, thereby promoting the uniform distribution of stress. At the same time, the fibers connect the local conductive sites of conductive carbon black in series to form a continuous three-dimensional topological framework network structure, and electrons can be transmitted in a long-range continuous path, and the conductivity of the electrode pole piece as a whole is enhanced.

[0051] Example 7

[0052] The mass ratio of silicon oxide negative electrode material: lithium ion battery performance enhancer: carbon black (SP): PAA (polyacrylic acid) = 80%: 3%: 7%: 10% in Example 4 was changed to 80%: 1%: 9%: 10%, and the rest was the same.

[0053] Example 8

[0054] The mass ratio of silicon oxide negative electrode material: lithium ion battery performance enhancer: carbon black (SP): PAA (polyacrylic acid) = 80%: 3%: 7%: 10% in Example 4 was changed to 80%: 5%: 5%: 10%, and the rest was the same.

[0055] Comparative Example 1

[0056] Different from Example 1, the bamboo fiber is directly heated to 800° C. at a heating rate of 5° C. / min under an argon atmosphere and calcined for 2 h to obtain a carbon fiber reinforcement.

[0057] Figure 3 The SEM images of the carbon fibers prepared in Example 1 and Comparative Example 1 of the present invention show that the biomass carbon fibers prepared in Example 1 have a hollow structure ( Figure 3 (a)), while the hollow structure of the carbon fiber prepared in Comparative Example 1 collapsed ( Figure 3 (b)).

[0058] Comparative Example 2

[0059] Different from Example 1, no oxidizing agent is added in step (1).

[0060] Comparative Example 3

[0061] Different from Example 1, no oxidant is added in step (1).

[0062] Figure 4 The SEM images of the precursors prepared in step (1) of Example 1, Comparative Example 2 and Comparative Example 3 of the present invention show that the precursor prepared in Example 1 has a hollow structure ( Figure 4 (a)), while the hollow structures of the precursors prepared in Comparative Examples 2 and 3 collapsed ( Figure 4 (b) Figure 4 (c)).

[0063] Comparative Example 4

[0064] The difference from Example 4 is that the lithium ion battery performance enhancer in Example 4 is replaced by the enhancer prepared in Comparative Example 1.

[0065] Comparative Example 5

[0066] The mass ratio of silicon oxygen negative electrode material: lithium ion battery performance enhancer: carbon black (SP): PAA (polyacrylic acid) = 80%: 3%: 7%: 10% in Example 4 was replaced with silicon oxygen negative electrode material: carbon black (SP): PAA (polyacrylic acid) = 80%: 10%: 10%, and the rest was the same.

[0067] Figure 8The SEM images (a) of the electrode surface of Example 4 of the present invention after 50 cycles at 0.5C and the SEM image (b) of the electrode surface of Comparative Example 5 after 50 cycles at 0.5C are shown. It can be seen from the figure that the electrode of Example 4 to which the lithium ion battery performance enhancer of the present invention is added has only tiny fine lines on the surface after 50 cycles, but comparative example 5 to which the lithium ion battery performance enhancer of the present invention is not added has large cracks on the surface after 50 cycles. This shows that the fiber can inhibit crack propagation through the "bridging" effect. When cracks propagate in the matrix, the fibers can locally enhance the crack area and limit the propagation of the cracks by interacting with the cracks.

[0068] Conductivity test: Based on the Kelvin four-wire method principle, the conductivity is tested using a four-probe powder conductivity tester.

[0069] The test results of the conductivity of the negative electrode sheets of Example 4 and Comparative Example 5 under different pressures are as follows: Fig. 9 It can be seen that the conductivity of Example 4 is better than that of Comparative Example 5.

[0070] Performance Testing

[0071] The assembled half-cell was left to stand at room temperature for 12 hours before constant current charge and discharge test and rate performance test. The constant current charge and discharge test was carried out at 30°C and 0.2C, and the rate performance test was carried out at 0.1C, 0.2C, 0.5C, 1C and 2C respectively. The battery cycle performance and rate performance test results of Example 4 and Comparative Example 5 are shown in FIG. Fig.10 , Fig.11 It can be seen that the battery cycle performance and rate performance of Example 4 are better than those of Comparative Example 5.

[0072] In the half-cell, the silicon-oxygen electrode is used as the positive electrode. The test process of the expansion rate of the silicon-oxygen electrode after lithium insertion is as follows: the thickness of the positive electrode sheet before the battery assembly is L1; after the battery charge and discharge cycle is completed after the 10th discharge cycle and the 50th discharge cycle, the battery is disassembled to take out the positive electrode sheet and measure the thickness L2 at the same place. Figure 7 The thickness of the negative electrode sheets of Example 4 and Comparative Example 5 before the cycle, after 10 cycles and after 50 cycles, it can be seen that the thickness change of the negative electrode sheet of Example 4 is less than that of Comparative Example 5. The expansion rate of silicon-oxygen electrode after lithium insertion % = (L2-L1) / L1×100%.

[0073] Verification result analysis:

[0074] Table 1 Test results of electrode expansion rate of Example 4 of the present invention and Comparative Example 3

[0075] Expansion rate after 10 turns Expansion rate after 50 cycles Example 4 16.3% 21.1% Comparative Example 5 31.4% 75.6%

[0076] The lithium ion battery performance enhancer obtained by the present invention is used in lithium ion batteries, and the electrode expansion rate test is carried out, and the test results are shown in Table 1. The electrode expansion rate of the lithium ion battery in Example 4 of the present invention after 10 cycles and 50 cycles is significantly less than that of the comparative example 5. The main reason is that the lithium ion battery performance enhancer of the present invention is a carbon fiber with a hollow structure, which helps to disperse the stress generated by the electrode expansion and reduces the capacity reduction phenomenon caused by the material fragmentation during the charging and discharging process. And the enhancer is mixed with the active material to form a three-dimensional topological framework network structure, which can establish a good link with the active material and the binder, realize the construction of a better electron transmission network, and improve the conductivity of the material. At the same time, the lithium ion battery performance enhancer of the present invention can play a role in collecting microcurrents between the active material particles and between the active material particles and the current collector, thereby reducing the contact resistance of the electrode, reducing the battery polarization, and promoting the infiltration of the electrolyte into the pole piece, thereby effectively solving the problems of low capacity, short cycle life and poor cycle stability of lithium ion batteries in the prior art.

[0077] Table 2 Charge and discharge test results of Examples 4-8 of the present invention and Comparative Examples 4-5

[0078]

[0079] As shown in Table 2, the first discharge capacity and first efficiency of Example 4 are better than those of Example 5 and Example 6. This is because after being treated at a specific carbonization temperature, the biomass carbon fiber can maintain a hollow structure and have good electrical conductivity, thereby effectively improving the cycle performance and rate performance of the battery, while also improving the first coulombic efficiency and capacity of the battery.

[0080] Example 4 is better than Example 7 and Example 8 because of the difference in the content of the reinforcing agent, which directly affects the three-dimensional topological framework network structure formed by mixing with the active material. In Example 7, the proportion of the reinforcing agent is relatively small, resulting in the failure to form a good structural system in the local area, and the battery rate performance is reduced; in Example 8, the proportion of the reinforcing agent is relatively large, resulting in local accumulation of carbon fiber materials, resulting in the blockage of ion transmission channels, thereby causing the battery performance to decline.

[0081] The rate performance of Example 4 is significantly better than that of Comparative Example 5 because the lithium ion battery performance enhancer of the present invention has good conductivity.

[0082] It should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solutions of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solutions of the present invention, which should be included in the scope of the claims of the present invention.

Claims

1. A lithium ion battery performance enhancer, characterized in that: The lithium-ion battery performance enhancer is biomass carbon fiber, which is a hollow structure with micropores on the surface; the lithium-ion battery performance enhancer can be mixed with active substances to form a three-dimensional topological framework network structure.

2. The lithium ion battery performance enhancer according to claim 1, characterized in that: The micropores are obtained by high-temperature carbonization; the wall thickness of the biomass carbon fiber is 0.0001 μm to 20 μm, the diameter is 0.01 μm to 50 μm, the length is 5 μm to 100 mm, and the aspect ratio is not less than 2.

3. The lithium ion battery performance enhancer according to claim 1, characterized in that: The active material is one or more of graphite negative electrode materials or silicon-based negative electrode materials.

4. A method for preparing a lithium ion battery performance enhancer according to any one of claims 1 to 3, characterized in that: The method comprises the following steps: (1) mixing an oxidant and an oxidizing aid evenly, adding biomass fibers, stirring at a certain temperature, washing with alcohol, and drying to obtain a precursor; (2) calcining the precursor under an inert atmosphere to obtain biomass carbon fiber, i.e., the lithium ion battery performance enhancer.

5. The method for preparing a lithium ion battery performance enhancer according to claim 4, characterized in that: The oxidant is one or more of sodium hydroxide, potassium hydroxide, sodium chlorite, sodium hypochlorite, and hydrogen peroxide; the oxidizing aid is one or more of acetic acid, citric acid, and phosphate buffer.

6. The method for preparing a lithium ion battery performance enhancer according to claim 4, characterized in that: The biomass fiber is one or more of the biomass native fibers of Malvaceae, Bombaxceae, Urticaceae, Palmaceae, and Gramineae, biomass regenerated fibers, and biomass synthetic fibers.

7. The method for preparing a lithium ion battery performance enhancer according to claim 4, characterized in that: The alcohol is one or more of methanol, ethanol, propylene glycol, butylene glycol, pentanediol and hexanediol.

8. The method for preparing a lithium ion battery performance enhancer according to claim 4, characterized in that: The mass ratio of the biomass fiber to the oxidant is 1:2 to 1:100; the mass ratio of the oxidant to the oxidizing aid is 1:1 to 1:

50.

9. The method for preparing a lithium ion battery performance enhancer according to claim 4, characterized in that: The drying temperature is 5°C to 120°C, and the drying time is 0.01h to 120h; the calcination temperature is 100°C to 1200°C, and the calcination time is 0.01h to 120h.

10. A negative electrode slurry for a lithium ion battery, characterized in that: The negative electrode slurry is added with the lithium ion battery performance enhancer according to any one of claims 1 to 3 or the lithium ion battery enhancer prepared by the method according to any one of claims 4 to 9, and the lithium ion battery performance enhancer accounts for 0.0001 to 10% of the total mass of the negative electrode slurry.